Chemotherapy May Influence Esophageal Lugol Chromoendoscopy Severity: A Retrospective Cohort Study and Literature Review - Hsu, Wen‐Hung; Lin, Chien‐Chieh; Shih, Hsiang‐Yao; Chan, Leong‐Perng; Wang, Hui‐Ching; Chen, Yi‐Hsun; Hsu, Yu‐Chung; Hsieh, Hui‐Min; Wu, I‐Chen (The Kaohsiung journal of medical sciences, 2025)
ABSTRACT Lugol chromoendoscopy is widely used for screening esophageal squamous cell neoplasms (ESCNs) and evaluating dissection margins during endoscopic submucosal dissection (ESD). However, morphological variations may arise following treatment for synchronous cancers. This study aimed to assess the impact of chemotherapy on Lugol chromoendoscopy findings during both screening and ESD. From August 2009 to March 2024, ESCN patients undergoing esophageal ESD were enrolled. Lugol chromoendoscopy findings were analyzed based on four criteria: iodine staining, lesion size, margin assessment, and the pink‐color sign. Findings from screening endoscopy and ESD were compared, and medical records were reviewed for chemotherapy and radiation data. A literature review was also conducted to explore the potential effects of chemotherapy on Lugol chromoendoscopy findings. Among the 162 patients in this ESD cohort, 32 (19.8%) demonstrated notable differences between initial and follow‐up Lugol chromoendoscopy. Among them, 14 (43.8%) had undergone chemotherapy prior to ESD, while 26 received chemotherapy within 2 months before ESD. A significant proportion (53.8%) of chemotherapy‐treated patients exhibited faded chromoendoscopy findings (p < 0.01), despite no esophageal radiation exposure. Literature review findings supported our observation that chemotherapy may reduce Lugol voiding lesions. These findings suggest that chemotherapy influences lesion size and morphology during Lugol chromoendoscopy, underscoring the importance of careful timing and interpretation in these patients.